Uruguay : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2009)
This Selected Issues paper quantifies the importance of international food and oil price inflation for Uruguayan inflation. The paper employs the vector autoregressive (VAR) model and Phillips-curve estimations techniques to address these questions. Similar estimations are carried out for a broader set of emerging markets to put the Uruguayan results into an international context. The paper examines spillovers from commodity price increases to measures of core inflation, and reveals that world food prices have had a strong but stable impact on Uruguay's inflation.